2018
DOI: 10.1037/ocp0000050
|View full text |Cite
|
Sign up to set email alerts
|

Service workers’ chain reactions to daily customer mistreatment: Behavioral linkages, mechanisms, and boundary conditions.

Abstract: Drawing on the stressor-emotion model, we examine how customer mistreatment can evoke service workers' passive forms of deviant behaviors (i.e., work withdrawal behavior [WWB]) and negative impacts on their home life (i.e., work-family conflict [WFC]), and whether individuals' core self-evaluations and customer service training can buffer the negative effects of customer mistreatment. Using the experience sampling method, we collect daily data from 77 customer service employees for 10 consecutive working days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 88 publications
5
84
0
3
Order By: Relevance
“…Consistent with the theoretical role of work-family conflict as a stressor that elicits unpleasant emotional states (Edwards & Rothbard, 2000;Greenhaus & Beutell, 1985;Grzywacz, 2016), trait negative affect is positively associated with work-family conflict levels (Allen et al, 2012;Michel, Clark, & Jaramillo, 2011). Similarly, studies show a positive association between daily work-family conflict levels and state negative affect (Ilies, Schwind, Wagner, Johnson, DeRue, Ilgen, 2007;Chi, Yang, & Lin, 2016), as well as a positive association between daily work-family conflict levels and daily negative emotions, such as guilt, hostility, and anxiety (Livingston & Judge, 2008;Judge et al, 2006;Wagner et al, 2014). I therefore propose EWIF/EFIW will be associated with a synchronous increase in state negative affectivity.…”
Section: Episodic Work-family Conflict and Acute Strain Reactivitymentioning
confidence: 79%
“…Consistent with the theoretical role of work-family conflict as a stressor that elicits unpleasant emotional states (Edwards & Rothbard, 2000;Greenhaus & Beutell, 1985;Grzywacz, 2016), trait negative affect is positively associated with work-family conflict levels (Allen et al, 2012;Michel, Clark, & Jaramillo, 2011). Similarly, studies show a positive association between daily work-family conflict levels and state negative affect (Ilies, Schwind, Wagner, Johnson, DeRue, Ilgen, 2007;Chi, Yang, & Lin, 2016), as well as a positive association between daily work-family conflict levels and daily negative emotions, such as guilt, hostility, and anxiety (Livingston & Judge, 2008;Judge et al, 2006;Wagner et al, 2014). I therefore propose EWIF/EFIW will be associated with a synchronous increase in state negative affectivity.…”
Section: Episodic Work-family Conflict and Acute Strain Reactivitymentioning
confidence: 79%
“…In contrast, when studying supervisor incivility and coworker incivility in Western culture with low power distance, both sources might have a similar effect on employees such that the effect of coworker incivility might also spill over the nonwork domain just like supervisor incivility does (Ferguson, ). Although outsider incivility has not been examined in the previous literature as a potential predictor of work‐to‐family conflict, previous research found that other types of workplace mistreatment from outsiders (e.g., daily customer mistreatment) positively predicted work‐to‐family conflict (e.g., Chi, Yang, & Lin, ). Building on the theoretical argument and empirical findings, we believe that workplace incivility from supervisors, coworkers, and outsiders can all potentially deplete employee resources and predict work‐to‐family conflict in Western culture.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Third, we focused on hostile attribution bias as a moderator to clarify the boundary effect of mistreatment by patients on work meaningfulness and emotional dissonance. Given that mistreatment by patients has an irreversible negative influence on employees and causes them physical and mental harm [86], we call for future research to investigate positive individual characteristics (i.e., core self-evaluation) and positive organizational level conditions (i.e., caring climate, leader support) that may buffer service employees' emotional reactions to mistreatment by patients.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%